The Influence of Service Quality and Facilities on Loyalty Through Patient Satisfaction at Anggrek Pontianak Clinic - Nuri Purnama; Muhammad Ebuziyya Alif Ramadhan (SAINTIS Publishing, 2025)
This study examines the influence of service quality and facilities on loyalty through patient satisfaction at Anggrek Clinic in Pontianak. An associative approach was used with 100 respondents, and data analysis was conducted using Structural Equation Modeling (SEM), including Convergent Validity, Discriminant Validity, Construct Reliability, and hypothesis testing. The results indicate that service quality and facilities have a significant simultaneous influence on patient satisfaction (47.2%) and loyalty (53.3%). Specifically, service quality positively and significantly influences patient satisfaction, while facilities significantly influence patient satisfaction. Additionally, patient satisfaction has a direct positive influence on loyalty. However, service quality and facilities do not directly influence loyalty. Indirect effect analysis shows that both service quality and facilities positively influence loyalty through patient satisfaction as an intervening variable. Further research is recommended to expand the sample by involving different health clinics throughout West Kalimantan to improve the generalizability of the results. Further qualitative studies may provide deeper insights into patients' perceptions and experiences, which may help improve service quality, patient satisfaction, and loyalty in healthcare settings.